THE USE OF THE ANDROID-BASED SANG NILA UTAMA DIGITAL MUSEUM APPLICATION TO IMPROVE SKILLS USE PRIMARY SOURCE EVIDENCE - Bunari Bunari; Asyrul Fikri (KABILAH : Journal of Social Community, 2022)
Abstract: The low skills of students in reading and analyzing historical sources are caused by social restrictions due to the covid-19 pandemic. So that activities outside of school such as historical field trips are abolished. Responding to this issue, this study aims to determine whether there is an effect of using the Android-based Sang Nila Utama digital museum application on the skills of using primary source evidence for high school students in Pekanbaru City. Experimental research method with randomized pretest-posttest control group design is used as an approach in this study. The research subjects involved 96 students of SMA Negeri 1 Pekanbaru City who were selected through proportional sampling technique. The research data were collected through the use of primary source evidence skill test sheets which were arranged based on the research objectives. The data analysis of the research results was carried out with a quantitative descriptive approach through the t-test statistical test to see the effect of giving treatment to the variable. The research findings show that there is a significant effect of using the Android-based Sang Nila Utama digital museum application on the skills of using primary source evidence of high school students in Pekanbaru City which is confirmed by the t-test significance value of 0.000 or less than 0.05. The average posttest score between the control group and the experimental group showed a difference. So it was concluded that the use of the Android-based Sang Nila Utama digital museum application had a significant effect on students' primary source evidence use skills. Keywords: Android application, Sang Nila museum, use primary source evidence